2021
DOI: 10.1136/bmjopen-2020-044814
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the ABCDEF bundle on delirium, functional outcomes and quality of life in intensive care patients: a study protocol for a randomised controlled trial with embedded process evaluation

Abstract: IntroductionHospital mortality for critically ill patients has decreased significantly throughout the developed world over the past two decades, attributable to improvements in the quality of intensive care, advances in critical care medicine and technologies that provide long-term multiorgan support. However, the long-term outcomes of intensive care unit (ICU) survivors is emerging as a real issue. Cognitive and physical impairments suffered by ICU survivors are common including profound weakness, pain and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It can effectively stimulate the muscle neurons, inhibit muscle decomposition, promote the growth of axons in compensatory circulation, and help shorten the unconscious time of muscle to restore neuromuscular function[ 20 ]. According to the evaluation results, a progressive early rehabilitation training model developed for appropriate nursing interventions effectively improves the scientific nature of targeted nursing measures[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can effectively stimulate the muscle neurons, inhibit muscle decomposition, promote the growth of axons in compensatory circulation, and help shorten the unconscious time of muscle to restore neuromuscular function[ 20 ]. According to the evaluation results, a progressive early rehabilitation training model developed for appropriate nursing interventions effectively improves the scientific nature of targeted nursing measures[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Family engagement in patient's recovery and early contact with relatives represents an addition to the aforementioned ABCDE protocol. The latest research demonstrated that the ABCDEF protocol is more complete and has showed positive short term clinical outcomes including lower mortality, shorter stay in ICU and shorter hospitalization, as well as lower incidence of POD [32,33]. Alternative methods include music therapy and massage.…”
Section: Preventionmentioning
confidence: 99%
“…A 'bundle of cares' comprises a set of interventions that, when performed collectively, improve the effectiveness and quality of patient care (Sosnowski et al, 2021). The ABCDEF bundle or care bundle A (Assess, prevent, and manage pain; B Both Spontaneous Awakening Trials (SATs) and Spontaneous Breathing Trials (SBTs); C Choice of analgesia and sedation; D Delirium monitoring and management; E Early mobility and exercise; and F Family engagement and empowerment) has been developed and implemented in thousands of Intensive Care Units (ICUs) (Morandi et al,…”
Section: Introductionmentioning
confidence: 99%